The Effect of Information System User Satisfaction on Individual Performance (High School Case Study) - Ari Lestari (Jurnal Mantik, 2021)
Evaluation that can be used to assess system performance is performance evaluation based on user perceptions. Users in this system include End Users, namely computer operators from all units, and people who use the output of this system (including management and leadership), namely individuals involved with this system. Evaluation of the system according to user perceptions is very important, because they are the ones who should feel the needs and benefits of the system. Perception is a cognitive process experienced by everyone in understanding information about their environment, either through visions, feelings and experiences. To assess whether the applied information system is running as planned, a measurement is needed. This research uses the PIECES method (Performance, Information, Economy, Control, Efficiency, Services) to be able to answer problems. PIECES is a tool in analyzing computer-based information systems, which consists of important points that are useful as guidelines / references in analyzing the system